2018
DOI: 10.1111/febs.14468
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of altered mitochondria by autophagy is impaired in Lafora disease

Abstract: Lafora disease (LD) is a fatal neurodegenerative disorder caused mostly by mutations in either of two genes encoding laforin and malin. LD is characterized by accumulation of a poorly branched form of glycogen in the cytoplasm of neurons and other cells. We previously reported dysfunctional mitochondria in different LD models. Now, using mitochondrial uncouplers and respiratory chain inhibitors, we have investigated with human fibroblasts a possible alteration in the selective degradation of damaged mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Since the autophagy machinery is impaired, mechanisms that require this process are also affected in cellular and animal models of the disease. In this sense, we have recently described a defect in mitophagy, most likely due to defects in the initial steps of autophagosome formation [178]. Finally, we have also reported that oxidative stress is affected in the absence of a functional laforin-malin complex [179].…”
Section: Lafora Disease (Ld)mentioning
confidence: 76%
“…Since the autophagy machinery is impaired, mechanisms that require this process are also affected in cellular and animal models of the disease. In this sense, we have recently described a defect in mitophagy, most likely due to defects in the initial steps of autophagosome formation [178]. Finally, we have also reported that oxidative stress is affected in the absence of a functional laforin-malin complex [179].…”
Section: Lafora Disease (Ld)mentioning
confidence: 76%
“…In addition, because of impairment in autophagy, defective mitochondria were not removed by mitophagy, worsening mitochondrial dysfunction (Ref. 33). Therefore, as in the case of ULD, there is a correlation between the presence of oxidative stress and neuroinflammation in this form of PME.…”
Section: Lafora Disease (Ld Epm2 Omim #254780)mentioning
confidence: 99%
“…It seems that the accumulation of LBs is deleterious to the cell and affects different physiological pathways, for example, LD mice present altered autophagy and mitophagy (Refs 24 , 31 33 ) and signs of oxidative stress (Ref. 34 ).…”
Section: Lafora Disease (Ld Epm2 Omim #254780)mentioning
confidence: 99%
“…Activation of mTOR in laforin-deficient cells further activated serum/glucocorticoid-induced kinase 1 (SGK1), and suppression of SGK1 activity could lower glycogen accumulation, inhibited mTOR and rescued the autophagy defect (Singh et al, 2013). Defective autophagic flux could lead to inefficient glycophagy and build-up of Lafora bodies that have neurotoxic effects (Duran et al, 2014); additionally, was also associated with impaired mitophagy, increased mitochondrial fragmentation and ROS production, and decreased ATP levels in laforin- and malin-deficient cells (Roma-Mateo et al, 2015; Upadhyay et al, 2017; Lahuerta et al, 2018).…”
Section: The Role Of Autophagy In Glycogen Storage Disordersmentioning
confidence: 99%